2023
DOI: 10.1521/pedi.2023.37.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder (BPD) and Complex Posttraumatic Stress Disorder (CPTSD): A Network Analysis in a Highly Traumatized Clinical Sample

Abstract: Whether complex posttraumatic stress disorder (CPTSD) and borderline personality disorder (BPD) diagnoses differ substantially enough to warrant separate diagnostic classifications has been a subject of controversy for years. To contribute to the nomological network of cumulative evidence, the main goal of the present study was to explore, using network analysis, how the symptoms of ICD-11 PTSD and disturbances in self-organization (DSO) are interconnected with BPD in a clinical sample of polytraumatized indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Diagnostic items related to affect dysregulation are often equal ly endorsed across the disorders, and in network analyses these symptoms appear to be common in both CPTSD and BPD 3 . How ever, BPD is associated with high rates of impulsivity and suicidal and self injurious behaviours, while in CPTSD these characteris tics may be present, but do not occur as frequently as other CPTSD symptoms, nor as often as in BPD 4 .…”
Section: Is It Possible To Differentiate Icd-11 Complex Ptsd From Sym...mentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic items related to affect dysregulation are often equal ly endorsed across the disorders, and in network analyses these symptoms appear to be common in both CPTSD and BPD 3 . How ever, BPD is associated with high rates of impulsivity and suicidal and self injurious behaviours, while in CPTSD these characteris tics may be present, but do not occur as frequently as other CPTSD symptoms, nor as often as in BPD 4 .…”
Section: Is It Possible To Differentiate Icd-11 Complex Ptsd From Sym...mentioning
confidence: 99%
“…Thanos Karatzias 1,2 , Martin Bohus 3,4 , Mark Shevlin 5 , Philip Hyland 6 , Jonathan I. Bisson 7 , Neil P. Roberts 7,8 , Marylène Cloitre 9,10 Of the many protocols drafted and discussed during the meet ings, very few survived the criticisms of the group members and were proposed to external bodies for funding. The first very suc cessful initiative was the European First Episode Schizophre nia Trial (EUFEST), the largest randomized trial comparing the clinical effectiveness of second vs. first generation (haloperidol below 5 mg/day) antipsychotics in first episode schizophrenia spectrum patients 1 .…”
Section: Is It Possible To Differentiate Icd-11 Complex Ptsd From Sym...mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Diagnostic items related to affect dysregulation are often equally endorsed across the disorders and in network analyses appear to link CPTSD and BPD. 15 However, BPD is associated with high rates of impulsive, suicidal and self-injurious behaviours, whereas in CPTSD these characteristics may be present but do not occur as frequently as other CPTSD symptoms nor as markedly or persistently as those seen in BPD. 11 Indeed, addressing suicidal and self-injurious behaviours has been viewed as the defining concern and primary treatment target in BPD.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…To date there have been seven studies exploring the association between BPD and ICD-11 CPTSD using disorder-specific measures. These studies have been conducted in general population samples as well as in clinical samples of traumatised individuals and they include factor analysis, 9,10 latent class analysis [11][12][13] and network analysis 14,15 designs. All these studies concluded that there is a group of individuals who endorse criteria of both conditions, but CPTSD and BPD were generally found to be distinct disorders.…”
Section: The Evidence Basementioning
confidence: 99%